CURRENT ISSUES OF PENALTIES OF CRIMINAL OFFENSES IN UKRAINIAN LEGISLATION - Калюжний, Ростислав Андрійович; Бантишев, Олександр Федорович; Романюк, Богдан Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Review of the monograph by Ponomarenko Yu.A. «General theory of determining the punishment of criminal offenses».